Respiratory morbidity and mortality of traumatic cervical spinal cord injury at a level I trauma center in India - Sengupta, Deep; Bindra, Ashish; Kumar, Niraj; Goyal, Keshav; Singh, Pankaj Kumar; Chaturvedi, Arvind; Malhotra, Rajesh; Mishra, Ashwani Kumar (Spinal cord series and cases, 2021)
Study design Descriptive retrospective. Objectives To evaluate the burden of respiratory morbidity in terms of ventilator dependence (VD) days and length of stay in neurotrauma ICU (NICU) and hospital, and to determine mortality in patients with traumatic cervical spinal cord injury (CSCI) in a low middle-income country (LMIC). Setting Jai Prakash Narayan Apex Trauma Center (JPNATC), All India Institute of Medical Sciences (AIIMS), New Delhi, India. Methods A total of 135 patients admitted with CSCI in the NICU between January 2017 to December 2018 were screened. Information regarding age, gender, American Spinal Injury Association (ASIA) impairment scale (AIS), level of injury, duration of VD, length of NICU, hospital stay, and outcome in terms of mortality or discharge from the hospital were obtained from the medical records. Results A total of 106 CSCI patients were analyzed. The mean (SD) age of patients was 40 (±16) years and male: female ratio was 5:1. The duration of VD, duration of NICU, and hospital stay was a median of 8 days (IQR 1127), 6 days (IQR 1118), and 15 days (IQR 3127) respectively. Mortality was 19% (20/106). The mortality was significantly associated with poorer AIS score, VD, and duration of ICU and hospital stay. All patients were discharged to home only after they became ventilator-free. Conclusions The ventilator burden, hospital stay, and mortality are high in patients with CSCI in LMICs. Poor AIS scores, prolonged VD, ICU and hospital stay are associated with mortality. There is a need for comprehensive CSCI rehabilitation programs in LMICs to improve outcome.